2021
DOI: 10.1556/044.2021.00156
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the reasons for living in poverty in Hungary

Abstract: The question of what are considered the causes of poverty is often neglected in the literature of this area of research. This paper analyzes the attributes of poverty in Borsod-Abaúj-Zemplén County, Hungary, which is one of the most disadvantaged areas of the country. Research was carried out in 2011 and 2019 using the method of systematic data collection, making possible the comparison of the changing perceptions of poverty over time. The research objective is to discover whether, as is common in Eastern Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…A szegénység szubjektív érzete sokszor nem teljesen esik egybe a tényleges anyagi státusszal vagy az egyén lehetőségeivel (Koczan 2016;Majumdar, Chatterjee 2020;Síposné Nándori 2021). A legrosszabb helyzetben lévők, a prekariátushoz tartozók közös ismérve a bizonytalanság: foglalkoztatási tekintetben kiszolgáltatottak, nincsenek karrierkilátásaik, és nincs racionálisan tervezhető jövőképük (Standing 2012; Kelemen, Rakovics 2013; Mikle 2019), a gazdasági-társadalmi folyamatok veszteseinek tekinthetők.…”
Section: Szakirodalmi áTtekintésunclassified
See 1 more Smart Citation
“…A szegénység szubjektív érzete sokszor nem teljesen esik egybe a tényleges anyagi státusszal vagy az egyén lehetőségeivel (Koczan 2016;Majumdar, Chatterjee 2020;Síposné Nándori 2021). A legrosszabb helyzetben lévők, a prekariátushoz tartozók közös ismérve a bizonytalanság: foglalkoztatási tekintetben kiszolgáltatottak, nincsenek karrierkilátásaik, és nincs racionálisan tervezhető jövőképük (Standing 2012; Kelemen, Rakovics 2013; Mikle 2019), a gazdasági-társadalmi folyamatok veszteseinek tekinthetők.…”
Section: Szakirodalmi áTtekintésunclassified
“…A fentiek alapján és a szakirodalmi előzményeket (Rácz 2014;Szoboszlai 2004;Síposné Nándori 2021) gyelembe véve úgy látjuk, hogy a helyi diskurzusokban a szegregáció és általában a szegénység percepciója nem követi a tényleges térfolyamatokat; a "szegregátum" és a "cigányok" kifejezések lényegében a szegénység szinonimájaként jelentek meg, de nem kötődtek a roma kisebbség tényleges jelenlétéhez vagy a lakóhelyek homogenitásához. A szociális munkások, falu-és tanyagondnokok, mivel kapcsolatban állnak a külterületeken élőkkel, már jóval di erenciáltabban fogalmaztak, noha a tanulmányban tárgyalt területeket ők is azonosították az interjúk során, nem a "szegregátum" fogalmát vagy annak szinonimáit használták, hanem például a "problémás hely" (Győr2) vagy a "néhány szegény él ott" (Szeged4) fordulattal jellemezték azokat.…”
Section: Diszkusszióunclassified
“…According to the World Bank (2018), poverty is not only about income and consumption, but it is also linked to non-financial dimensions such as access to education, electricity, drinking water, and sanitation. Nandori (2021bNandori ( , 2021c states that the Covid-19 pandemic has affected public perceptions of poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Majumdar and Chatterjee ( 2020 ) found that non-social work students considered low education level as an individualist explanation in their study of perceptions of poverty, its causes, and future commitment to work with the poor. Similarly, Nandori ( 2021 ) argues that it is unclear whether certain factors are structural individual, or fatalistic, including “low level of income”, “hopelessness”, “low level of education”, “unemployment”, “debt” or isolation”. Finally, Calnitsky ( 2018 ) suggests that individualistic and structural explanations of poverty can interact: “Individualistic explanations of poverty become more complex when we invoke individual attributes that themselves have social causes” (p.3).…”
Section: Theoretical Approaches To Poverty Attributions and Brief Lit...mentioning
confidence: 99%